2004
DOI: 10.1159/000077342
|View full text |Cite
|
Sign up to set email alerts
|

<i>Mycoplasma pneumoniae</i> in Elderly Patients with Stroke

Abstract: Background and Purpose: Previous studies have suggested certain infections as potential risk factors for stroke. Chlamydia pneumoniae, an atypical respiratory pathogen, has been linked to atherosclerotic vascular diseases. Mycoplasma pneumoniae, another atypical respiratory micro-organism, can rarely cause stroke. We investigated whether serological markers of M. pneumoniae infection were associated with acute stroke or transient ischaemic attack (TIA) in elderly patients. Methods: This case-control study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Indeed, MP has been found in atherosclerotic plaques (9), and increased serum antibody of MP in patients with coronary artery disease has been reported (10), which raised the hypothesis that MP could promote atherosclerosis. However, although MP infection may be independently associated with the risk of subsequent ischemic stroke development (8), studies of the seroprevalence of MP in stroke patients and controls led to conflicting results (61, 62). Further investigations are needed to confirm that MP infection is an independent risk factor for stroke in the long-term and to better understand the relationships between MP infection and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, MP has been found in atherosclerotic plaques (9), and increased serum antibody of MP in patients with coronary artery disease has been reported (10), which raised the hypothesis that MP could promote atherosclerosis. However, although MP infection may be independently associated with the risk of subsequent ischemic stroke development (8), studies of the seroprevalence of MP in stroke patients and controls led to conflicting results (61, 62). Further investigations are needed to confirm that MP infection is an independent risk factor for stroke in the long-term and to better understand the relationships between MP infection and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, IgA-based diagnosis is less established than IgM- or IgG-based diagnosis, and persistently elevated IgA as indicator of chronic infection, although biologically plausible, has to be interpreted with caution. It has to be mentioned that differing figures concerning the seroprevalence of IgA antibodies to M. pneumoniae in elderly patients have been published, with seroprevalences up to 79% [8], [13]. However, the applied assay and the respective cut-off level for positivity is obviously important in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies found an association between M. pneumoniae infection and atherosclerosis [5], [6], [7]. However, others have presented discordant results, so that the role of M. pneumoniae in the pathogenesis of atherosclerosis must still be regarded as unknown [8], [9]. …”
Section: Introductionmentioning
confidence: 99%